Synthesis, Characterization and Stability Study of V(IV), Zr(IV), Rh(III), Pd(II), Cd(II) and Hg(II) Complexes with Pyrazol Derivative - Baghdad Science Journal (مجلة بغداد للعلوم, 2014)
In this work lactone (1) was prepared from the reaction of p-nitro phenyl hydrazine with ethylacetoacetate, which upon treatment with benzoyl chloride afforded the lactame (2). The reaction of (2) with 2-amino phenol produced a new Schiff base (L) in good yield. Complexes of V(IV), Zr(IV), Rh(III), Pd(II), Cd(II) and Hg(II) with the new Schiff base (L) have been prepared. The compounds (1, 2) were characterized by FT-IR and UV spectroscopy, as well as characterizing ligand (L) by the same techniques with elemental analysis (C.H.N) and (1H-NMR). The prepared complexes were identified and their structural geometries were suggested by using elemental analysis (C.H.N), flame atomic absorption technique, FT-IR and UV-Vis spectroscopy, in addition to magnetic susceptibility and conductivity measurements. Metal to ligand [M:L] ratio was obtained for all complexes in ethanol using molar ratio method, which gave comparable results with those obtained for the solid complexes. As well as the apparent stability constant of the complexes have been studied with the time and their color were stable for more than 4 hrs., furthermore the molar absorptivity have been calculated.